Efeito de dose única de vitamina D nas concentrações séricas de citocinas em mulheres idosas na pós-menopausa - Scalcon, Márcia Regina Rosa (2014)
Vitamin D is an important immunomodulator. Epidemiological studies have shown that vitamin D deficiency impairs the immune functions and participates in the pathogenesis of infectious and autoimmune diseases. Vitamin D supplementation has shown significant changes on circulating concentrations of inflammatory markers in different clinical conditions. However, the effect of single large-dose of vitamin D3 in immune system in elderly people remains unclear. We carried out a randomized, double-blind, placebo-controlled clinical trial to evaluate the possible benefic effect of single oral dose of 300.000 IU of vitamin D3 on inflammatory markers in elderly post-menopausal women. A total of 40 women aged over 60 years were selected to receive 300.000 IU of cholecalciferol (n = 20) or placebo (n = 20) at baseline. Serum 25-hydroxyvitamin D [25(OH)D] were similar in both group at baseline [16.4 ng/ml (± 3.8) in vitamin D group and 15 ng/ml (± 3.7) in placebo groups, p = 0.23]. Serum levels of IL-6, TNF-α and IL-10 were measured by ELISA at baseline, and 30, 60 and 90 days after intervention. In the vitamin D group, we found a significant median percent decline in levels of IL-6 (30.8%, p = 0.006) and TNF-α (48.6%, p < 0.0001), associated with a significant median percent increase in levels of IL-10 (68.4%, p < 0.0001) after 90 days. We concluded that a single oral dose of 300.000 IU of cholecalciferol, in the short time, is able to improve the cytokines profile in elderly women with vitamin D deficiency.